GROWTH OF Kielmeyera rubriflora INOCULATED WITH ARBUSCULAR MYCHORRIZAL FUNGI ON IRON MINING SUBSTRATES - Lara, Rodrigo de Oliveira; PARECIDA PEREIRA da silva, MICHELE APARECIDA; Oliveira, Paula Alves; Pereira, Israel Marinho; Grazziotti, Paulo Henrique (Floresta, 2019)
Mining results in major landscape changes. Restoring areas after exploitation of natural resources can be accomplished through adopting techniques used to optimize the restoration process. Among such techniques, planting seedlings of species adapted to adverse edaphoclimatic conditions and which have interspecific associations with microorganisms stand out. One of these indigenous species which occur in the Southern Espinhaço Mountain Range with potential for use in restoring degraded areas is Kielmeyera rubriflora (Spreng) Mart. Thus, the objective of this study was to evaluate the influence of inoculating arbuscular mycorrhizal fungi on the survival and growth of Kielmeyera rubriflora Cambess. on two substrates from iron mining. The experiment was carried out in a nursery of the UFVJM Plant Species Propagation Center (CIPEF) in a randomized block design and treatments arranged in a 2 x 2 factorial design, using two iron mining substrates and inoculated and uninoculated plants with five repetitions. The seedlings received 25 g of the soil-inoculum mixture of Paraglomus occultum (C. Walker) JB Morton & D. Redecker and Claroideoglomus etunicatum (WN Becker & Gerd) C. Walker & A. Schüßler at the transplantation time to 17 dm3 pots. Stem diameter and leaf number were influenced only by the main effects of substrate and inoculation, while plant height was influenced by the interaction between substrate and inoculation. Inoculation with mycorrhizal fungi in Kielmeyera rubriflora ensures survival, species growth and root development on both iron mining substrates and is a suggested strategy for planting in areas degraded by iron mining.